Influence of High-Pressure Water Injection on the Pore Structure of Anthracite Coal in Xinjing Coal Mine - Xiao, Zhiguo (ACS Omega, 2020)
[Image: see text] High-pressure water injection, as an important measure for coal and gas outburst prevention, is still under-researched, especially its mechanism on the coal pore structure. The anthracite samples taken from no. 3 coal seam in Xinjing coal mine were dried and injected with high-pressure water, after which their pore characteristics were studied by using mercury porosimetry (MP) and low-pressure N(2) gas adsorption (LP-N(2)GA). The results of MP showed that after the water was injected into the coal samples, the pore volume and the pore size of samples increased, but the specific surface area (SSA) remained almost unchanged. It could be concluded from LP-N(2)GA experiments that after the high-pressure water injection, the SSA of coal samples reduced greatly, but their pore size increased significantly. Through detailed analysis, the mechanism of high-pressure water injection on the coal pore structure is described as follows: the pores within the samples fracture after high-pressure water injection and the diameter of pores becomes bigger, resulting in increases in both the pore volume and the pore size. In addition, water molecules injected will stay at the end of micropores, so there is almost no change in the SSA, as indicated by MP testing results. However, the SSA of coal samples decreased significantly in the LP-N(2)GA testing. This is because it is really difficult to evaporate water molecules staying in the micropores by heating because of the strong interaction between water and coal. This study is helpful to further understand the mechanism of high-pressure water injection on preventing coal and gas outburst at the microlevel.